2008
DOI: 10.2500/aap.2008.29.3123
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms of tumor necrosis factor alpha−308 and interleukin-10−1082 among asthmatic Egyptian children

Abstract: Tumor necrosis factor (TNF) alpha-308 and interleukin (IL)-10(-1082) have potent inflammatory responses in the process of airway inflammation in asthma. The purpose of this study was to check for association of polymorphisms related to cytokine genes with susceptibility and severity of bronchial asthma in Egyptian children. Blood samples of 69 asthmatic children receiving treatment and follow-up at the Allergy and Respiratory Medicine Unit, Mansoura University Children Hospital, Mansoura, Egypt, were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
3
24
0
3
Order By: Relevance
“…For instance, Xie (2012) suggested that the IL-10 -627C/A polymorphism was associated with asthma risk in Chinese children. A study conducted in Egyptian asthmatic children showed a significantly higher frequency of the IL-10 -1082 GG genotype in these patients (Zedan et al, 2008). However, there have also been studies reporting contradictory results: Kim et al (2011) reported that the frequency of genotypes and alleles of the IL-10 promoter polymorphisms (-1082G/A, -819C/T, and -592C/ A) did not differ significantly between Korean asthmatic children and controls.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…For instance, Xie (2012) suggested that the IL-10 -627C/A polymorphism was associated with asthma risk in Chinese children. A study conducted in Egyptian asthmatic children showed a significantly higher frequency of the IL-10 -1082 GG genotype in these patients (Zedan et al, 2008). However, there have also been studies reporting contradictory results: Kim et al (2011) reported that the frequency of genotypes and alleles of the IL-10 promoter polymorphisms (-1082G/A, -819C/T, and -592C/ A) did not differ significantly between Korean asthmatic children and controls.…”
Section: Discussionmentioning
confidence: 94%
“…The studies were excluded for the following reasons: reviews (N = 5), duplicated data (N = 3), non-case-control study (N = 5), no useful data (N = 2), irrelevant to pediatric asthma (N = 12). Finally, a total of 16 case-control studies comprising 2494 cases and 2160 controls were included in this meta-analysis to evaluate the association between IL-10 promoter polymorphisms and the risk of pediatric asthma (Zhang et al, 2002;Schubert et al, 2006;Li et al, 2006Li et al, , 2007Movahedi et al, 2008;Zedan et al, 2008;Undarmaa et al, 2010;Hussein et al, 2011;Kim et al, 2011;Wei et al, 2011;Xie, 2012;Ji et al, 2013;Smolnikova et al, 2013;Tan et al, 2013;Hussein et al, 2014;Xu et al, 2014). Eleven of the studies were performed in an Asian population, and three and two of the remaining studies were conducted in people of African and Caucasian descent, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately half of the studies, including one genome-wide association study, claim no effect [17,18,19,20,21,22,23,24,25,26,27,28,29], while others argue for a significant association, either protective or predisposing [30,31,32,33,34,35,36,37,38,39,40]. Regarding atopic rhinitis and dermatitis, the association of TNFα -308 polymorphisms has rarely been studied [14,41,42,43].…”
Section: Introductionmentioning
confidence: 99%